Analisis Resepsi dalam Film Bulan Terbelah di Langit Amerika - Surawijaya Ningsih, Bunga (Program Studi Komunikasi dan Penyiaran Islam, Fakultas Dakwah, IAI Al-Qodiri Jember, 2022)
The power and ability of film has become an audio-visual communication medium that reaches many social segments and is enjoyed by people of all ages and social backgrounds. It is from this basis that convinces experts that films have the potential to influence their audiences. There are various themes in a film's content, two of which are about race and religion. Bulan Terbelah di Langit Amerika, for example. After this film aired, there were pros and cons to the message in the film. Because Bulan Terbelah di Langit Amerika places more emphasis on contemporary Islamic issues that are currently in the world's spotlight, including Islamophobia. The film Bulan Terbelah di Langit Amerika shows Islamophobia, which is a form of ignorance of Western society towards Islam. This film shows the treatment of American society that demeans Islam such as religious intolerance, suspicion and hatred towards Muslims and anti-pluralism attitudes towards other teachings. This research is about how the reception analysis in the film Bulan Terbelah di Langit Amerika is based on the Indonesian Christian Youth Movement and the Catholic Youth Movement. The purpose of this study is to describe the reception of the Indonesian Christian Youth Movement and the Catholic Youth Generation to the film Bulan Terbelah di Langit Amerika. By using a descriptive qualitative approach, the researcher chose to conduct research in Jember Regency. The result, from the non-Muslim youth studied, namely the Indonesian Christian Youth Movement Youth and the Catholic Youth Movement, and both had the same results. Where both are in the dominant hegemonic or receive messages in the film Bulan Terbelah di Langit Amerika.